PENINGKATAN KUALITAS PENYUSUNAN LAPORAN KEUANGAN DENGAN APLIKASI ZET ACCOUNTING PADA KAMPUNG SAYUR KLAMPOK PANDANARUM BLITAR - Arfiq, Arfiq Safitri Ningsih; Dyah Pravitasari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
In the Kampung Sayur, in the Klampok Hamlet, Pandanarum Village, Blitar Regency, theyhave their own financial reports. The financial statements recorded are very simple. due tolack of knowledge of good financial reports, they only write income and expensetransactions. If the financial statement records are presented properly, it can help theKampung Sayur business in information needs for investors and increase capital in a bankto develop the vegetable village business. Therefore, this study aims to determine thebenefits of the financial application of zet accounting in an effort to improve the quality ofthe preparation of financial reports in the Kampung Sayur Klampok Pandanarum Blitar.The method used in this research is descriptive qualitative. Data collection techniques usedare observation, interviews with documentation. The research location is in the KampungSayur business, Klampok village, Pandanarum village, Sutojayan district, Blitar district.Financial reports that used to still use the manual method by hand written using paper orledgers. with the zet accounting application, it can help the preparation of good andcorrect financial reports for the Kampung Sayur. Profit/loss reports and changes in capitalwill be clearly visible and appear automatically after we enter transaction data that hasoccurred in a period.